Indicators of the Anthropocene: is there a case for conservation?. (March 2014) - Jordan, Hannah; Prosser, Colin
<x xml:space="preserve">Abstract</x> The Earth's atmosphere, biosphere and lithosphere are increasingly being modified by human activity. Given this anthropogenic influence on the natural environment, the case for recognizing an Anthropocene Epoch has recently been made and there is ongoing debate as to whether, and how, to formally characterize and define such an epoch. As a contribution to this debate, this article explores whether or not the landscapes, deposits, landforms and key marker horizons that may be used to characterize and define an Anthropocene Epoch could, and should, be identified and conserved in the same manner as other parts of the geological succession. Anthropogenic features pose a conservation challenge, however, as they often cross cut existing conservation frameworks which tend to focus on the natural, historic or cultural environment. Developing a coherent approach to the conservation of the indicators of an Anthropocene Epoch would, therefore, require an integrated system of describing, auditing and designating features for conservation. A major benefit of such an approach would be the opportunities for interdisciplinary collaboration between the wide range of researchers interested or involved in studying and conserving the record of anthropogenic activity.